Analisis Pengaruh Reward dan Punishment Terhadap Disiplin Kerja Karyawan Di Hotel Radisson Blu Bali Uluwatu - Ni Komang Erlinda Junika Swari; I Gusti Ngurah Sanjaya; I Gusti Ketut Gede (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the effect of Reward and Punishment on Employee Work Discipline at Radisson Blu Bali Uluwatu Hotel. The study was motivated by the importance of employee work discipline in supporting the achievement of organizational goals. This research employed a quantitative approach using an associative method. The population consisted of 152 permanent employees of Radisson Blu Bali Uluwatu Hotel, with a sample of 61 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 27. The results showed that Reward had a positive and significant effect on Employee Work Discipline, with a t-value of 4.573 and a significance value of 0.000. Punishment also had a positive and significant effect on Employee Work Discipline, with a t-value of 11.654 and a significance value of 0.000. Simultaneously, Reward and Punishment had a positive and significant effect on Employee Work Discipline, with an f-value of 638.154 and a significance value of < 0.001. The coefficient of determination (R²) of 0.955 indicated that Reward and Punishment explained 95.5% of the variation in Employee Work Discipline, while the remaining 4.5% was influenced by other factors outside this study. The findings indicate that the proper and consistent implementation of Reward and Punishment can improve Employee Work Discipline. Therefore, the company is expected to maintain the consistent implementation of Reward and Punishment to enhance Employee Work Discipline.